Biotechnical portfolio management of mixed-species forests - Brunette, Marielle; Dragicevic, Arnaud; Lenglet, Jonathan; Niedzwiedz, Alexandra; Badeau, Vincent; Dupouey, Jean-Luc (Springer Science and Business Media LLC, 2017)
Based upon the historical data—obtained from the French National Forest Inventory—on the tree species’ productivities, assimilated to be a measure of return on investment, as well as on their variances as sources of risk, we apply the portfolio selection theory in order to optimize the species distributions in France. We thus determine the optimal return-risk combinations of tree species and map them per administrative department. We also estimate the resistance of optimal portfolios using the species’ probabilities of presence. Our results show that greater weights in the optimal portfolios match with higher probabilities of presence, implying that foresters have incentives to invest in the most resilient species.
Keywords: [QFIN.PM]Quantitative Finance [q-fin]/Portfolio Management [q-fin.PM]; forest management; [QFIN.RM]Quantitative Finance [q-fin]/Risk Management [q-fin.RM]; [QFIN.PM] Quantitative Finance [q-fin]/Portfolio Management [q-fin.PM]; Bioeconomics; climate change; [QFIN.RM] Quantitative Finance [q-fin]/Risk Management [q-fin.RM]; portfolio management; mixed-species forest